2006
DOI: 10.1002/jat.1163
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of isothiocyanates towards N‐nitrosamine‐induced DNA damage in the single‐cell gel electrophoresis (SCGE)/HepG2 assay

Abstract: The aim of this study was to investigate the protective effect of isothiocyanates towards N-nitrosamine-induced DNA damage in the single-cell gel electrophoresis (SCGE)/HepG2 assay. None of the isothiocyanates (ITCs) concentrations tested in the presence or absence of formamidopyrimidine-DNA glycosylase (Fpg) caused DNA damage per se. Combined treatments of HepG2 cells with phenethyl isothiocyanate (PEITC), allyl isothiocyanate (AITC) or indol-3-carbinol (I3C) and N-nitrosopyrrolidine (NPYR) or N-nitrosodimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 36 publications
1
21
2
2
Order By: Relevance
“…In contrast to findings of Arranz et al (31), who described the PEITC-caused reduction of SSB induced by N-nitrosamine in HepG2 cells, we have not seen any PEITC-caused reduction of SSB induced by IQ. Our results are in accordance with findings of García et al (44), who found a weak protective effect of PEITC towards N-nitrosodibutylamine or N-nitrosopiperidine oxidative DNA damage in the single cell gel electrophoresis (SCGE)/HepG2 assay.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to findings of Arranz et al (31), who described the PEITC-caused reduction of SSB induced by N-nitrosamine in HepG2 cells, we have not seen any PEITC-caused reduction of SSB induced by IQ. Our results are in accordance with findings of García et al (44), who found a weak protective effect of PEITC towards N-nitrosodibutylamine or N-nitrosopiperidine oxidative DNA damage in the single cell gel electrophoresis (SCGE)/HepG2 assay.…”
Section: Discussioncontrasting
confidence: 99%
“…Modulation of the clastogenic effect of mitomycine C and cyclophosphamide by PEITC was detected in bone marrow cells of mice (30). The protective effect of isothiocyanates towards N-nitrosamine induced DNA damage was proved in HepG2 cells by the single-cell gel electrophoresis assay (31).…”
Section: Introductionmentioning
confidence: 97%
“…In our previous studies, the protective effect of ITCs alone towards Nnitrosodimethylamine (NDMA) and N-nitrosopyrrolidine (NPYR) was evaluated (Arranz et al, 2006). Our results showed that the protective effects of ITCs tested were higher towards NPYR induced oxidative DNA damage than against NDMA.…”
Section: Introductionmentioning
confidence: 69%
“…I3C exerted greater inhibition on coumarin hydroxylase activity than PEITC. The antimutagenic effects of cruciferous vegetables extracts against food N-nitrosamines have been previously evaluated in our laboratory (Ikken et al, 1998) as well as the protective effect of PEITC, AITC and I3C towards NDMA or NPYR-induced oxidative DNA damage (Arranz et al, 2006). The results of theses studies reported that broccoli extracts exhibited strong antimutagenic effects against NDBA (43.5%) and NPIP (39%) by the Ames test.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation